Eksistensi dan Paradigma Keilmuan Manajemen Pendidikan Islam (MPI) - M Yusuf (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2018)
If we pay attention to the real conditions among educational institutions around us, especially Islamic-based educational institutions, as if we see these institutions managed as they are without activities that stand out in relation to managerial processes, even if there is no managerial activity at all from the manager. The existence of an educational institution is very instrumental in answering what is, what has actuality, everything that is experienced and emphasizes that something exists, and reaches the perfection of an educational institution. Islamic education is determined by the basic theories, methodologies and praxis established in formal objects and material objects. Formal Objects of Management science Islamic education is the science of management (the science of management), for example from Frederick Winslow Taylor. As a science, the formal approach used by Islamic Education Management is scientific research in the field of management